2022
DOI: 10.1093/pm/pnac183
|View full text |Cite
|
Sign up to set email alerts
|

Brief Mindfulness-Based Cognitive Behavioral Therapy is Associated with Faster Recovery in Patients Undergoing Total Knee Arthroplasty: A Pilot Clinical Trial

Abstract: Objective To assess whether brief mindfulness-based cognitive behavioral therapy (MBCBT) could enhance the benefits of total knee arthroplasty (TKA) in improving pain and pain-related disability. Specifically, to determine (1) whether patients who received MBCBT differed from matched controls who received treatment as usual (TAU) on post-surgical pain outcomes, and (2) whether changes in pain catastrophizing, depression, and/or anxiety explained the potential effects of MBCBT on pain outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Based on their ability to heighten healing processes, whether they can assist in efforts to improve cartilage regeneration efforts or minimize inflammation that can worsen structural damage should be examined. In the interim it appears adding a mindfulness-based intervention to neuromuscular exercises and others appears to reduce pain intensity and improve function, balance and quality of life in adults with knee osteoarthritis [55], in addition to speeding up recovery post knee joint replacement therapy [58].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their ability to heighten healing processes, whether they can assist in efforts to improve cartilage regeneration efforts or minimize inflammation that can worsen structural damage should be examined. In the interim it appears adding a mindfulness-based intervention to neuromuscular exercises and others appears to reduce pain intensity and improve function, balance and quality of life in adults with knee osteoarthritis [55], in addition to speeding up recovery post knee joint replacement therapy [58].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is recommended that future studies test interventions focusing on other relevant behavioral and cognitive targets in addition to physical activity (e.g., social support, pain catastrophizing, pain self-efficacy) to effectively enhance recovery and long-term outcomes after spine surgery. For example, recent studies have suggested that reductions in catastrophizing and fear of movement mediate the beneficial effects of CBT on improving pain and function after a variety of surgeries, including knee surgery [ 67 ] and spine surgery [ 68 ]. Interventions targeted at such crucial psychosocial process variables and delivered in “high-risk” samples of patients (e.g., those who are sedentary or high in catastrophizing and fear of movement) may optimize the beneficial outcomes of such treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately this should be identified and treated because even if replacement surgery is forthcoming a high number of cases continue to feel dissatisfied. In addition to careful evaluation of depression subtypes [49], to improve six month outcomes, those with excess preoperative pain profiles, as well as opioid users [39,50] who are depressed and those with low self efficacy scores that align with opioid use or dysfunctional cognitions should be preferentially targeted [51][52][53].…”
Section: Journal Of Aging Research and Healthcarementioning
confidence: 99%